Application of ANN in Agarwood Oil Grade Classification - Saiful Nizam, Tajuddin; Nurlaila, Ismail; Mohd Hezri, Fazalul Rahiman; Mohd Nasir, Taib; Nor Azah, Mohd Ali; Mailina, Jamil (2014)
This paper presents the application of Artificial Neural Network (ANN) in agarwood oil grade classification. The work involved of the extraction of chemical compounds by GC-MS, identification the significant chemical compounds using Z-score, generating the synthetic data using a dedicated formulae and application of ANN classification. The ANN classification is performed and its performance is measured using accuracy, sensitivity and specificity. The result showed that the performance of ANN classification for original GC-MS data is increasing when the data is added with synthetic data. This study showed that the ANN application in this study required a large number of sample size for it to have high accuracy in classification.